คุณลักษณะด้านสมบัติเชิงกลและคุณภาพน้ำโลหะของโลหะผสมทองแดงไร้ตะกั่ว - วันทนี สิทธิหล่อ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
CAC406 (Cu-5wt%Sn-5wt%Zn-5wt%Pb) has been commonly used for water supply equipments but the WHO guideline on lead dissolution in tap water which is less than or equal to 0.01 mg L-1 must be satisfied. Substitution of lead in CAC406 is categorized into two ways; one is bismuth or bismuth-selenium bronze (lead free bronze) and the other is Si brass. This research studied structure-properties relation, machinability and melt quality of lead free copper alloys comparing with CAC406. High temperature tensile testing at high strain rate (1/s) was carried out to simulate machinability. It was found that tensile strength and elongation of lead free bronze alloys were decreased sharply when the temperature was increased to above 100 ºC. This demonstrates the poorer machinability when machining load is applied at the work piece. For Si brass, although the tensile strength at high temperature is rather high but the machinability is inferior to CAC406. Deoxidation process by copper-phosphorus alloy, which determines the melt quality in clean melt, is vital in the casting process of copper alloys. The capability to evaluate phosphorus content through cooling curve method was investigated for on-site testing during deoxidation process. Phosphorus content can be evaluated by considering the decrease in the liquidus temperature when the phosphorus content is increased.